2022
DOI: 10.1002/advs.202202800
|View full text |Cite
|
Sign up to set email alerts
|

Portable Cold Atmospheric Plasma Patch‐Mediated Skin Anti‐Inflammatory Therapy

Abstract: Although plasma is a promising technology in various fields, its clinical application is restricted by several limitations. A cold atmospheric plasma (CAP) patch is fabricated to help overcome hurdles, especially when treating skin diseases. This patch has surface dielectric barrier discharge, which generates reactive oxygen species (ROS) and reactive nitrogen species (RNS) on a flexible polymer film surface on which the embedded electrode induces a locally strong electric field. The effect of the CAP patch on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…Furthermore, different studies have suggested CAP for the treatment of cancer [37,38]. Atopic dermatitis, psoriasis, and herpes zoster, among others, are further skin diseases in which CAP has been successfully applied [23,[39][40][41][42]. Recently, Karrer et al [43] used a jet plasma device in a prospective, randomized, controlled, split-face trial to assess its safety and efficacy in the treatment of acne vulgaris.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, different studies have suggested CAP for the treatment of cancer [37,38]. Atopic dermatitis, psoriasis, and herpes zoster, among others, are further skin diseases in which CAP has been successfully applied [23,[39][40][41][42]. Recently, Karrer et al [43] used a jet plasma device in a prospective, randomized, controlled, split-face trial to assess its safety and efficacy in the treatment of acne vulgaris.…”
Section: Discussionmentioning
confidence: 99%
“…CP has also shown efficacy against psoriasis, an inflammatory skin condition with abnormal keratinocyte activity that exhibit aberrant MAPK, PI3K/Akt, STAT3 and NFκB pathway [270]. Although the molecular pathway responses to CP in psoriasis are not well characterised, CP inhibits STAT3 activation and significantly remedy inflammatory and epidermal hypertrophic pathologies in a psoriasis mouse model [271,272].…”
Section: Direct Comparisons Between Malignant Cells and Between Malig...mentioning
confidence: 99%
“…15 To counteract such challenges, flexible DBD plasma has recently been developed to conform to intricate structures and irregular surfaces, enabling effective plasma treatment in complex environments. The flexibility of the plasma could provide incomparable advantages compared to rigid structure plasma sources and can be applied in various applications such as wound healing, 16 food processing, 17,18 and surface disinfection. 19 The production cost of flexible DBD plasma devices is affected by the material choice of the dielectric and conductive electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional methods for electrode deposition of thin film flexible plasma are ink-jet printing and screen-printing of conductive inks such as copper or silver on the dielectric surface. 16,30 However, the conductive inks require a post-deposition thermal sintering process at high temperatures, thus creating mild deformation on the paper structure. 31 Recently, Mazzeo et al used metalized paper for DBD plasma, with the paper layer acting as the dielectric barrier and the metal layer engraved into an electrode structure.…”
Section: Introductionmentioning
confidence: 99%